Crystallization and polymorphism in polypropylene/polyamide 6/layered silicate ternary nanocomposites. Issue 1 (25th March 2018) - Motamedi, Pouyan; Bagheri, Reza
Abstract: polypropylene (PP)/polyamide 6 (PA6)/layered silicate nanocomposites have a great capacity for combining the advantages of a low‐cost commodity matrix with those of an engineering thermoplastic reinforced with a nanometric filler. Although the morphology and mechanical properties of these systems are well studied, the amount of knowledge available on their crystallization behavior is scarce. This study is focused on how composition, processing procedure, and crystallization method affect the phase structure in both polypropylene and polyamide 6 in the ternary PP/PA6/layered silicate nanocomposites. Several variations of the 2 polymers, their blends, and their composites were studied using differential scanning calorimetry, X‐ray diffraction, and scanning electron microscopy. It was observed that the α/β/γ phase ratio in PP and α/γ ratio in PA6 are strongly affected by the presence of both layered silicate and compatibilizer, as well as the method of solidification. In addition, PA6 was observed to be a more effective nucleating agent for PP, compared with layered silicate. Abstract : Crystallographic structure of semicrystalline polymers may affect their physical and mechanical properties. Polymorphism and crystal structure of engineering polymers, such as polypropylene and polyamide 6, have therefore been the subject of numerous studies. However, the effect of various processing parameters on the crystallization behavior of these polymers has not been adequately studied, nor has the simultaneous effect of additives, compatibilizers, and processing procedure on the polymorphism and crystallinity in multiphase thermoplastic blends. This study aims to address this shortcoming by a comprehensive analysis of nanocomposites based on polypropylene/polyamide 6 blends.